Olea europaea leaves extract downregulate Newcastle disease virus gene expression in cancer cells - Salih, Rajaa Hindi (Iraqi Journal of Cancer and Medical Genetics, 2017)
Many researches have been made to find antiviral agents from natural sources. Leaf of Olea europaea (OLE) is one of the most important medicinal plants, as it is a well-known source of different phytochemicals. This study was carried out to investigate the effect of using Olea europaea leaves extract on the level of viral gene expression (M and F) in Hela cell line by using the qRT-PCR. Also, we examined the adding of interferon-beta ( IFN-b ) as an antivirus factor and analyzed the expression of viral and IFN-b genes to identify viral targets for OLE extract. First, we propagated the virus in embryonated chicken eggs and showed to kill embryos in different times intervals (less than 72 hours) with marked sever hemorrhage in infected embryos, and agglutination activity reflects titer (1024) and 1×10 6.4 (TCID50). Hela cells were cultured and different concentration of OLE extract was added; cell viability was measured by MTT assay. Gene expression showed that the expression of the viral gene was downregulated in the present of OLE extract. Pretreatment with IFN-b downregulated viral gene expression higher than the extract, also evaluated the IFN-b concentration by ELISA assay. OLE can be considered as antivirus agent and used this property to help in control Newcastle disease.